PRODUTIVIDADE DE GENÓTIPOS DE FEIJÃO COMUM DO GRUPO CARIOCA CULTIVADOS NA REGIÃO DO ECÓTONO CERRADO/PANTANAL - ROJAS, Matheus Gonçalves; NAGEL, André Lucas; SANTOS, Carla Medianeira Giroletta; SILVA, Jeferson Antonio dos Santos; GUEDES, Gabriela; CORREA, Agenor Martinho (ANAIS DO ENIC, 2020)
-